Comparative analysis of productive chain the production of cocoa between Colombia and Ecuador - García P, Milena; Montaño Quintero, Luís Felipe; Montoya R, Alexandra (Revista de Ciencias Agrícolas, 2012)
After reviewing the state of Ecuadorian and Colombian cocoa value chains, is proposed an improvement of the competitiveness of Colombian agrifood chain by means of an analysis about the elements that support the performance and sustainability of the chain, in both countries. The methodology examines Michael Porter’s assumptions, through a comparative analysis using Benchmarking. It facilitates the identification of critical success factors and it let to suggest lines of action regarding the role of government, institutions and private sector at national level.